Tubal Pathology in Infertility - Tjahyadi, Dian (Indonesian Journal of Obstetrics & Gynecology Science, 2025)
Infertility is a complex reproductive issue which requires thorough evaluation and targeted intervention. A key cause of female infertility is fallopian tube dysfunction, which plays role in egg transport and fertilization. Structural damage to the tubes, including blockages, adhesions, and deformities, significantly reduces fertility potential. One major cause of tubal disease is sexually transmitted infections, especially Chlamydia trachomatis and Neisseria gonorrhoeae, which can lead to pelvic inflammatory disease (PID). 1 In regions where Mycobacterium tuberculosis infection is still prevalent, genital tuberculosis is another contributor to tubal disease, causing inflammation and eventual obstruction. Chronic infection promotes scarring, narrowing, and complete obstruction of the fallopian tubes. Additionally, endometriosis can also exacerbate tubal dysfunction by creating adhesions and disrupting normal tube anatomy